Alexandra-Maria Vrînceanu, Feminist Ideology and Translated Literature, Iaşi: Institutul European, 2024, 244 p. - Mihaela MUDURE (Studia Universitatis Babeş-Bolyai. Philologia)
The young scholar Alexandra-Maria Vrînceanu has an extensive experience as a freelance interpreter and certified translator at Cartea Românească Publishing Press and Black Swan Publishing Press. Since 2019 Vrînceanu has been teaching seminars and practical courses on translation, discourse analysis, and English grammar at the Faculty of Letters of “Alexandru Ioan Cuza” University in Iaşi, Romania.